AZD8233 antisense oligonucleotide targeting PCSK9 does not prolong QT interval. Issue 11 (10th June 2022) - Rekić, Dinko; Azarov, Ivan; Knöchel, Jane; Sokolov, Victor; Nilsson, Catarina; Wernevik, Linda; Han, David; Rydén‐Bergsten, Tina; Ebrahimi, Ahmad; Dota, Corina; Carlsson, Björn
Abstract : Aims: AZD8233 is a proprotein convertase subtilisin/kexin type 9 (PCSK9) antisense oligonucleotide under development for treatment of hypercholesterolaemia. A prespecified concentration‐QT analysis was performed based on data from a single ascending dose study that was prospectively designed to act as a TQT study substitute. Methods: Subcutaneous single doses ranging from 4 to 120 mg were evaluated in 73 adult healthy male subjects. Time‐matched 12‐lead digital ECG and plasma concentrations ( n  = 15) were measured at baseline and up to 48 hours after dose in each subject. The analysis was performed using a linear mixed effect model, where change from baseline QTc (ΔQTc) was a dependent variable and time‐matched AZD8233 concentration was an independent variable. Results: The high clinical exposure scenario was defined as 1.7‐fold the expected C max following an assumed therapeutic dose of 60 mg, which corresponds to AZD8233 plasma concentration of 1.39 μg/mL. Estimated placebo‐corrected and baseline‐adjusted QTcF interval (ΔΔQTcF) at this concentration was −2.2 ms (90% CI: −4.11, −0.28). Furthermore, the upper 90% ΔΔQTcF confidence interval was estimated to be below 10 ms at all observed concentrations. Conclusion: As the effect on ΔΔQTcF is below the threshold for regulatory concern (10 ms), it can be concluded that AZD8233 does not induce QTcF prolongation at the high clinical exposure scenario.